2016
DOI: 10.1371/journal.pone.0149052
|View full text |Cite
|
Sign up to set email alerts
|

Behçet's: A Disease or a Syndrome? Answer from an Expression Profiling Study

Abstract: Behçet’s disease (BD) is a chronic, relapsing, multisystemic inflammatory disorder with unanswered questions regarding its etiology/pathogenesis and classification. Distinct manifestation based subsets, pronounced geographical variations in expression, and discrepant immunological abnormalities raised the question whether Behçet’s is “a disease or a syndrome”. To answer the preceding question we aimed to display and compare the molecular mechanisms underlying distinct subsets of BD. For this purpose, the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(39 citation statements)
references
References 39 publications
3
36
0
Order By: Relevance
“…CCL4 (C-C motif chemokine ligand 4) belongs to the cytokine family and is involved in immunoregulation and inflammation. It has been reported that CCL4 is associated with BD immunopathogenesis [ 42 ]. In the majority of VKH cases, the expression of another family member CCL17 was lower in cerebrospinal fluid than in serum, which indicated its potential function in VKH [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…CCL4 (C-C motif chemokine ligand 4) belongs to the cytokine family and is involved in immunoregulation and inflammation. It has been reported that CCL4 is associated with BD immunopathogenesis [ 42 ]. In the majority of VKH cases, the expression of another family member CCL17 was lower in cerebrospinal fluid than in serum, which indicated its potential function in VKH [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…This mutation causes decreased A20 expression and results in immune dysregulation with increased NF-κB activity in response to TNF-α ( 10 ); it is also proposed as a risk factor for autoimmune disorders ( 11 , 12 ). Additionally, TNFAIP3 is reported to be linked with susceptibility to BD ( 4 , 13 , 14 ). Intestinal Behcet's disease is considered a polygenic disease with a strong genetic background, but its diagnosis is still based on typical intestinal ulcers and manifestations of systemic BD ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Behcet's disease (BD) is an inflammatory vascular disease causing superficial thrombophlebitis and deep vein thrombosis. [1][2][3] Violating arterial system, especially PAA is rare in BD. This case was complicated with PAA and PE.…”
Section: [ ( F I G _ 1 ) T D $ F I G ]mentioning
confidence: 99%